Analysing the Relevant Competency Traits for IBF Graduates Towards Improved Employability - Shahabudin, Najibah Khairiyah; Ishak, Amal Hayati (The journal of contemporary issues in business and government, 2022)
The concept of competency is crucial since it enables us to establish a systematic hiring procedure in order to evaluate applicants (Barbosa, I, Freire, C, & Santos, M. P., 2017, Ali, N. A. M., & Kasim, N., 2019). But it still has an issue whereby there is too many research on traits for Islamic finance graduates’ employability. Thus, the purpose of this paper is to analyse the right set of competencies as a scale to be used in Islamic financial institutions (IFIs). Using a qualitative method of library research, this paper found the right set of competencies for the graduates’ employability are interpersonal skills, knowledge abilities, Islamic values, self- management, time management, cognitive-analytical, cognitive-technical, enthusiasm, and language. Thus, this paper promotes the idea of a set of competencies for IBF graduates that meet the job vacancy demand of Islamic financial institutions.